Análise da formação de descargas atmosféricas baseada na aplicação do modelo do leader bidirecional - Raphael Batista Borges Louro (2017)
This work shows a study about the prediction of a cloud-to-ground discharge formation based on the bidirectional leader model. After a literature review, computational routines were developed based on the charge simulation method to simulate the evolution of the discharge channel. It should be noted that the computational tool, adapted from the basic formulation of Mazur and Ruhnkes work, has a lower computational cost in the representation of the physical system due to the methodology developed for the estimation of the electric quantities associated to the process. Furthermore, the tool uses a distinct formulation to include the effect of an irregular soil relief. The tool was applied to simulate the lightining channel formation until the attachment process, and to analyze situations of practical interest such as the presence of tower, upward leader and branches in the stepped leader in conditions of plane relief and similar to the region around the Morro do Cachimbo Station